EQUITABLE ACCESS TO HEALTH SERVICE IN BANYUWANGI - , Lusi Herawati; , Prof. Dr. Sunyoto Usman ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Getting equitable health care is a basic right for citizens. Government is responsible to ensure equitable care is given. This research was conducted to analyze community discrepancy in access to health services in general hospitals and health center (Puskesmas) in Banyuwangi, East Java Province, Indonesia. This research was executed by identifiying community accessibility to health facilities services by using travel time and transport mode choice as an indicator (distinguishing user groups). Data analysis technique that are used in this research have been operationalized in Flowmap software. This tool helps to calculate the catchment area of existing health facility and provide the scenario for improving the accessibility of community to health facility service (by different transport modal choices: walking, becak and public transport for the considered poor group and motorcycle and car for the considered non-poor group with different travel time thresholds of 30 minutes, 30 - 60 minutes and more than 60 minutes). The result of the research shows, for the poor group, by walking, general hospital services can be reached by 4,8% poor people in 30 minutes, 5,6% within 30 - 60 minutes and 89,4% need more than 60 minutes. By using becak, 7,6% poor people can access general hospital service in 30 minutes, 21% within 30 â 60 minutes and 71,4% need more than 60 minutes. By using public transport, 40% poor people can access general hospital service in 30 minutes, 33,5% within 30 â 60 minutes and 26% need more than 60 minutes. In the other hand for the nonpoor group, by using motorcycle, 51,2% non-poor can access general hospital service in 30 minutes, 33,7% within 30 â 60 minutes and 15,1% need more than 60 minutes while by using car, 55,2% non-poor can access general hospital service in 30 minutes, 32,1% within 30 â 60 minutes and 12,7% need more than 60 minutes. From the analysis concluded that there is an accessibility difference between poor and non-poor group. The accessibility to the health facilities of poor group is lower than the non-poor group. This condition occurred because prevailing policies to provide equitable health care have paid unsufficient attention to accessibility aspects of poor groups